NPY genes and AGC kinases define two key steps in auxin-mediated organogenesis in Arabidopsis - Cheng, Youfa (National Academy of Sciences, 2008)
Auxin is an essential regulator of plant organogenesis. Most key genes in auxin biosynthesis, transport, and signaling belong to gene families, making it difficult to conduct genetic analysis of auxin action in plant development. Herein we report the functional analysis of several members of 2 gene families (NPY/ENP/MAB4 genes and AGC kinases) in auxin-mediated organogenesis and their relationships with the YUC family of flavin monooxygenases that are essential for auxin biosynthesis. We show that 5 NPY genes (NPY1 to NPY5) and 4 AGC kinases (PID, PID2, WAG1, and WAG2) have distinct, yet overlapping, expression patterns. Disruption of NPY1 does not cause obvious defects in organogenesis, but npy1 npy3 npy5 triple mutants failed to make flower primordia, a phenotype that is also observed when AGC kinase PID is compromised. Inactivation of YUC1 and YUC4 in npy1 background also phenocopies npy1 npy3 npy5 and pid. Simultaneous disruption of PID and its 3 closest homologs (PID2, WAG1, and WAG2) completely abolishes the formation of cotyledons, which phenocopies npy1 pid double mutants and yuc1 yuc4 pid triple mutants. Our results demonstrate that NPY genes and AGC kinases define 2 key steps in a pathway that controls YUC-mediated organogenesis in Arabidopsis.